E-Business and Entrepreneurial Growth among Indonesian Young Entrepreneur - Cahyadi, Asep Indra (Journal of Business Management Education (JBME), 2020)
The purpose of this study is to study the perceptions of young entrepreneurs regarding the use of e-business and entrepreneurial growth. The survey was conducted at the Indonesian Young Entrepreneurs Association of Higher Education (HIPMI PT) in Bandung with a population of 31 entrepreneurs. The results of the study using a questionnaire revealed business research and entrepreneurial growth in the Indonesian Young Entrepreneurs Association of Higher Education in Bandung depending on the category which is quite good, it can be attributed to large respondents who can implement e-business better with better entrepreneurial growth. Business processes at the SMEs scale are expected to use e-business more intensively so as to enhance entrepreneurial growth.